DEVELOPMENT OF THE MICROVASCULAR BED AND TISSUE STRUCTURES OF THE LARGE INTESTINE DURING PROLONGED PESTICIDE POISONING - Nosir A. Khasanov; Khabibulla Kh. Pulatov; Behzod Kh. Shermatov; Akhror U. Khujabekov (Scholar Express Journals, 2023)
The ongoing worldwide intensive chemicalization of agriculture leads to the fact that annually a large number of various foreign chemicals (xenobiotics), including pesticides, enter the planet's biosphere, that is, the environment for the habitat of all living things, including humans. As a result of careless handling of pesticides, as well as accidental or intentional ingestion of the drug, acute and subacute poisoning occurs [1]. Most researchers [1] note that in acute poisoning with pesticides, especially insecticides and acaricides, there is an increased blood filling of intraorgan vessels, swelling of their walls and hemorrhage in the gastrointestinal mucosa. We have studied the effect of new pesticides "Neoron" and "Sumi-alpha" on the morphological state of the microvasculature and tissue structures of the colon in acute poisoning. LD50 for rats with intragastric administration of "Neoron" was 950 mg/kg and "Sumi-alpha" - 75 mg/kg, respectively. The drugs were administered once intragastrically using a metal probe at a dose of 1/2 LD50. at the rate of 1.0 ml of an aqueous solution of the pesticide per 100 animal weight. Control animals in the same volumes received distilled water at the rate of 1.0 ml per 100 weight.
Keywords: pesticides; poisoning; Neoron